ENSURING CONTINUITY OF EDUCATION THROUGH CROSS-PLATFORM INTEGRATION: A COMPARATIVE ANALYSIS OF MODERN LEARNING MANAGEMENT SYSTEMS (LMS) (Multidisciplinary Journal of Science and Technology, 2026)
This article fundamentally investigates the role of cross-platform integration in modern e-learning systems and its significance in ensuring educational continuity. Within the framework of the study, modern Learning Management Systems (LMS) are comparatively analyzed, examining their operational efficiency across various devices (Android, iOS, Windows) and operating systems. Based on the analysis of cross-platform solutions in the Finnish and South Korean educational models, proposals based on cloud architecture for the national education system of Uzbekistan are put forward.